Development of an integrated HIV, STI and Teenage pregnancy prevention programme in Vhembe District of Limpopo Province, South Africa - Rammela, Mukovhe (My University, 2025)
Background: In South Africa, there are several health care services provided at the primary level of health care dedicated to addressing adolescents' sexual and reproductive needs. These services often face challenges such as limited resources, lack of funding and insufficient training for healthcare providers, which hinder their ability to provide integrated care. Additionally, cultural stigma and lack of privacy are factors which deter adolescents from seeking help. Purpose: The study sought to develop an integrated Human Immunodeficiency Viruses (HIV), sexually transmitted infections (STI), and teenage pregnancy prevention programme among youth in the Vhembe district of Limpopo province. Methods: This study employed a comprehensive multiphase mixed-methods strategy structured across three interconnected phases to ensure a robust exploration of the subject matter. The journey began with Phase 1, where a comprehensive literature review was conducted. This foundational step laid the groundwork for the entire research by synthesizing existing knowledge and identifying gaps that warranted further investigation. Moving into Phase 2, the research adopted a concurrent triangulation mixed methods approach divided into two stages. This innovative phase was pivotal, culminating in the development of a conceptual framework interwoven with qualitative and quantitative findings. The study created a comprehensive understanding of the issues at hand by integrating, comparing, and interpreting data from diverse sources. In the Final Phase, the findings from Phase 2 were subjected to rigorous analyses, including a Political, Environmental, Social, and Technological (PEST) analysis and a Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis. The insights gleaned from these analyses served to inform the design of integrated programs geared toward preventing HIV, sexually transmitted infections (STIs), and teenage pregnancies. To ensure the efficacy of these proposed programs, a consultation was held with the Reduce the Risk (RTR) Coalition, which included a diverse group of stakeholders and experts. This collaborative effort aimed to validate the approach taken. Quantitative data were gathered through questionnaires distributed to 112 respondents at selected clinics in the Vhembe district, while qualitative insights were captured through simultaneous face-to-face interviews. As the data from Phase 2 were analyzed, qualitative findings underwent thematic analysis to identify key patterns and themes, while the quantitative data were processed using SPSS software. This detailed analytical process aimed to provide a nuanced understanding of the results, ultimately enriching the study's findings and contributing to more effective public health interventions. Results: AYFS has been evaluated in depth across eight WHO global standards for quality healthcare services for adolescents, with areas of success and areas for improvement identified. Provider competency reveals a disparity, with a majority (67.0%) of healthcare providers trained in effective communication with adolescents. In comparison, significantly fewer have received specific training in AYFS (16%) or on Pre-Exposure Prophylaxis (PrEP) (25.9%), underscoring the need for a more balanced approach to training focus. Ineffective implementation and monitoring of existing interventions were also identified as barriers. Several respondents cited insufficient resources for HIV PrEP implementation. Institutional barriers, such as staff shortages, also hinder HIV PrEP integration into family planning. A significant challenge is the lack of knowledge among healthcare workers regarding HIV PrEP and its benefits. Several facilitators were identified for successfully integrating HIV PrEP into family planning services, including community support, motivated staff, technical support and stakeholder collaboration. By effectively integrating these services, we can significantly diminish stigma and improve access to quality sexual health care in rural areas. This, in turn, is likely to result in better health outcomes, including reduced rates of HIV infection, as well as increased access to contraception. Conclusion: The findings of this study support the need for the integration of HIV, STIs, and pregnancy prevention services, given that all stakeholders demonstrated a readiness to participate in such a programme. The stakeholders agreed that such a programme would be an effective way of reducing HIV, STI transmission and teenage pregnancies while also providing reproductive health services. The stakeholders have expressed a desire to work collaboratively to ensure the success of the integrated programme. To implement the integrated programme, stakeholders could establish joint training sessions for healthcare providers to ensure consistent service delivery. They could also create a centralized platform for sharing resources and best practices. Additionally, regular community outreach events could be organized to raise awareness and encourage participation in the programme.
PhD (in Public Health)
Department of Public Health
Keywords: Human Immunodeficiency Viruses; UCTD; Integrated prevention programme; Sexually transmitted infection; Teenage pregnancy; Teenage pregnancy -- South Africa -- Limpopo; Pregnancy -- South Africa -- Limpopo; HIV (Viruses) -- South Africa -- Limpopo; Sexually transmitted diseases -- South Africa -- Limpopo; Sexually transmitted diseases -- Prevention